Variations of planktonic chlorophyll-a in relation to environmental factors in a Mediterranean Coastal System (Iskenderun Bay, Northeastern Mediterranean Sea) - Polat, S.; Terbiyik, T. (Universiti Kebangsaan Malaysia, 2013)
Chlorophyll-a is one of the most widely used parameters to estimate trophic state of an aquatic environment. The purpose of this study was to investigate the changes in the planktonic chlorophyll-a concentrations in relation to environmental parameters in the east part of Iskenderun Bay (Northeastern Mediterranean Sea). Monthly measurements of chlorophyll-a and inorganic nutrients were done on two transects at 6 stations across the Bay. In addition, variations in temperature, salinity and some meteorological factors were also investigated, their correlation with chlorophyll-a were analyzed. The highest chlorophyll-a concentration (3.8 μg L-1) was found on coastal transect nearer to the bay. The first peak in chlorophyll-a occurred in May, a second smaller peak was recorded in September. The correlation of chlorophyll-a was significantly positive for Silicate-Si and Nitrate+nitrite-N but not important for Phosphate-P. No dramatic increase in chlorophyll-a levels was encountered in the area during the study period. It was concluded that, due to the hydrodynamic structure of the area, the land-based effects influence chlorophyll-a dynamics.